Configuración e implementación de redes lan mediante router cisco en el laboratorio de redes y mantenimiento de la Universidad Técnica de Cotopaxi extensión La Maná, año 2014 - Alban Yanchapanta, Edgar Fabian (2015)
Currently communications are the main technological hub of a company or institution, which has been developing more and new projects of this nature, in order to improve or speed up communications and especially that these flow better and safer inside and outside organizations....